Seven weeks of combined strength and power training during the competitive season in high-level amateur soccer: A randomized-controlled trial - Faude, O.; Roth, R.; Di Giovine, D.; Donath, L.; Zahner, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Speed and power abilities are considered important prerequisites for match performance in soccer. Scientific studies addressing specific strength and power training methods are scarce so far, particularly when conducted during the competitive season. We therefore investigated the effects of a 7 weeks combined strength and power training program during the competitive season on various fitness parameters in high-level amateur soccer players. Methods: Sixteen male soccer players (age: 22.5 (SD 2.5) y, height: 1.79 (5.3) m, weight: 76.8 (6.1) kg) from one team of the third Swiss league were randomly stratified (strata: one-repetition maximum (1-RM), 10 m sprint time) to either a combined strength training (CST, N = 8) or a control (CON, N = 8) group. The intervention was conducted twice per week within an in-season period of 7 weeks. CST comprised strength exercises (uni- and bilateral half squats and calf raises with additional weights) combined with plyometrics and/or sprints (5 to 10 m). CON performed technical and tactical training during the same time period. Before and after the training period, several physical fitness parameters were assessed: 1-RM (half squat), isometric peak strength and rate of force development (RFD, leg press, uni- and bilateral), vertical jump height (countermovement jump, CMJ (uni- and bilateral); drop jump, DJ), 10 and 30 m sprint times, agility testing with the ball, and intermittent endurance performance (yo-yo intermittent recovery test 1). Results: Players attended on average 10.9 (1.1) training sessions during the 7 weeks period. Large significant test x group interactions were found for 1-RM (p < 0.001, effect size (ES, partial eta squared) = 0.76), bilateral CMJ (p < 0.001, ES = 0.58), CMJ with the left leg (p = 0.003, ES = 0.51), and drop jump reactivity index (p = 0.003, ES = 0.57) with increases after CST (+3 to 18%) and similar or decreased values (+0.6 to -7.7%) in CON. Although not significant (0.09 . p < 0.40) comparable results were observed in several other parameters (isokinetic peak strength and RFD, CMJ with right leg, DJ, 30 m sprint time, and intermittent endurance) with effect sizes indicating at least medium effects (0.06 . ES < 0.19). No relevant test x group interaction was observed for agility testing and 10 m sprint. Discussion: It is concluded that a 7 weeks combined strength and power training can improve relevant physical prerequisites compared to routine technical and tactical training in high-level amateur soccer players during the competitive season. The medium effects in sprint time, jump heights and intermittent endurance need further verification in randomized-controlled trials with more participants.